Assessing the Reuse Potential of Industrial Heritage using GIS-AHP: A Case Study of El Hamma’s Industrial District, Algiers Algeria - Bouaziz , Samia; Guechi, Imen (Future Science, 2024)
Industrial heritage, encompassing both tangible and intangible evidence of industry history, holds profound cultural and historical significance. However, this heritage is often abandoned and neglected, as seen in the El Hamma district of Algiers, the capital of Algeria. The study aims to determine the priority order for the preservation of these industrial buildings, emphasizing the methods and priorities necessary to protect this invaluable heritage. The research methods involve introducing a comprehensive framework for evaluating the potential reuse of industrial heritage through a GIS-AHP methodology, assessing factors such as historical importance and architectural value. Employing the methodology of Weighted Overlay Analysis (WOA) in ArcGIS, the study categorizes sites for preservation or potential demolition, providing stakeholders with valuable insights into conservation priorities. The research results underscore the crucial importance of heritage preservation in maintaining local identity and promoting sustainable urban development. These findings highlight the need for an interdisciplinary strategy that balances economic growth with heritage conservation, ensuring the cultural and historical significance of the El Hamma district is safeguarded.